1976
DOI: 10.1677/joe.0.0680419
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Adrenergic Receptor Activity, Cyclic Amp and Lipolysis in Adipose Tissue of Hypothyroid Man and Rat

Abstract: Lipolysis and intracellular levels of cyclic AMP of adipose tissue from man and rat in both hypothyroid and euthyroid states were studied in response to stimulation by catecholamines in vitro. Hypothyroid patients were studied before and after treatment, and were also compared with euthyroid obese controls. The experimental group of rats was rendered hypothyroid by the addition of 2.9 mM-propylthiouracil to their drinking water, and their status confirmed by plasma thyroid function tests. Evidence for alpha-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Likewise, the sensitivity of the alpha-receptor appears to be normal in adult diabetics. Our techniques are sufficiently sensitive to demonstrate changes in catecholamine receptor sensitivity, and in hypothyroidism we have confirmed the results of Rosenqvist et al [2] on release of glycerol, demonstrating an increased alpha-receptor sensitivity in adipocytes, which can be reversed by treatment of patients with l-thyroxine [4]. It is therefore unlikely that changes in catecholamine receptor sensitivity are responsible for the increased flux of plasma fatty acids that is frequently observed in adult diabetes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Likewise, the sensitivity of the alpha-receptor appears to be normal in adult diabetics. Our techniques are sufficiently sensitive to demonstrate changes in catecholamine receptor sensitivity, and in hypothyroidism we have confirmed the results of Rosenqvist et al [2] on release of glycerol, demonstrating an increased alpha-receptor sensitivity in adipocytes, which can be reversed by treatment of patients with l-thyroxine [4]. It is therefore unlikely that changes in catecholamine receptor sensitivity are responsible for the increased flux of plasma fatty acids that is frequently observed in adult diabetes.…”
Section: Discussionsupporting
confidence: 86%
“…In hypothyroidism there is increased activity of the alpha-receptor of adipocytes so that stimulation with catecholamines (noradrenaline or adrenaline) results in an impaired increment of glycerol compared either to euthyroid controls [2] or to hypothyroid tissue stimulated by a predominant beta-agonist such as isoprenaline [3]. The receptor defect in hypothyroidism is reversible with thyroxine therapy [4] and may contribute to the low levels of plasma fatty acids observed in hypothyroidism.…”
mentioning
confidence: 99%
“…Many studies in cells from different tissues have indicated that thyroid hormones are inactive in this regard (28)(29)(30)(31)(32)(33). On the other hand, T3 in vitro has been found to increase the cAMP concentration in spermatozoa from Macaca mulatta (34), and thyroxine to act similarly in rat osteogenic sarcoma cells in culture (17).…”
Section: Effects Of Alprenololmentioning
confidence: 99%
“…Catecholamines seeril to be physiologically important mediators for lipid 'mijbilization in these cells (6)(7)(8)(9)(10)(11)(12)(13). Beta adrenergic stimulation increases adenylate cyclase activity, raises cyclic AMP, and enhances the cyclic AMP-dependent processes such as lipolysis, whereas alpha adrenergic activation, in general, has opposite effects (6)(7)(8)(9)(10)(11)(12)(13). These observations support the hypothesis put forward by Robison et al (14) that some cell types have both alpha and beta adrenoceptors that mediate opposite effects on cyclic AMP and cell function.…”
Section: Introductionmentioning
confidence: 99%